O estudante de hoje financiado pelo profissional do amanh\~a: Proposta de um sistema nacional de financiamento estudantil com pagamentos vinculados à renda futura - funcionamento e fonte de recursos - Paulo A. Meyer M. Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– It is proposed a broad two-tier income-contingent financing system for postsecondary students, designed for public and private providers and consisting of both income-contingent loans (ICLs) and income share agreements (ISAs), with repayments to be collected by the Federal Revenue System (FRS). Both students enrolled in tuition-free publicly run programmes and students enrolled in fee-paying programmes would be able to contract either ICLs or ISAs offered by both public and private financial institutions within the parameters defined by law and by regulatory instruments, without necessarily linking their ICLs and ISAs to the payment of tuition fees or other educational charges. In the case of students with no fees to pay (either because enrolled at tuition-free public institutions or attending fee-paying programmes totally or partially funded by the Government), the cost of the financial aid provided by the State would be added to the balances of the ICL or ISA accounts linked to their respective social security numbers. ICLs and ISAs contracted with duly certified financial institutions would also be accounted for in the balances of the individual accounts of students who resorted to such financing tools, and the law or other regulatory instrument must define debt ceilings. Repayments would be made in two different ways. Either debtors advance repayments directly to the organisation regulating the proposed system or postpone them and pay the debt through the tax system. This paper proposes legislative reforms to set the grounds to the new student funding system, which includes incorporating the tax-like contribution to the national tax system (as the way to involve the FRS in the repayment collection) as well as making the constitutionally mandatory free-of-charge provision in the public sector compatible with the collection of the new tax-like contribution from all graduates from public universities and VET institutions.
Keywords: G59; H27; I22; 330; higher education; vocational education and training; student financing; cost sharing in postsecondary education; income-contingent financing